1988
DOI: 10.1042/bj2560245
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a high-molecular-mass form of calcitonin [procalcitonin-(60–116)-peptide] and its corresponding N-terminal flanking peptide [procalcitonin-(1–57)-peptide] in a human medullary thyroid carcinoma

Abstract: Four peptides derived from procalcitonin were isolated in high yield from an extract of a human medullary thyroid carcinoma. The peptides were identified as procalcitonin-(1-57)-peptide, procalcitonin-(60-91)-peptide (calcitonin), procalcitonin-(60-116)-peptide and procalcitonin-(96-116)-peptide (katacalcin). Determination of the amino acid sequence of procalcitonin-(1-57)-peptide has demonstrated that the Ala25-Ala26 bond in preprocalcitonin is the site of cleavage of the signal peptide. Procalcitonin-(60-116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Into the C cells, procalcitonin is cleaved into calcitonin, katacalcin and a proteic residue, and it is not released into the blood stream of healthy individuals [1]. PCT is known as a good biological diagnostic marker for severe sepsis, or septic shock in critically ill patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Into the C cells, procalcitonin is cleaved into calcitonin, katacalcin and a proteic residue, and it is not released into the blood stream of healthy individuals [1]. PCT is known as a good biological diagnostic marker for severe sepsis, or septic shock in critically ill patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a 7-kDa 57-residue amino-terminal proCT cleavage peptide, N-proCT, was identified in rat and human C cells (19,20). Like C-proCT, N-proCT is secreted in equimolar amounts with CT (19).…”
Section: Introductionmentioning
confidence: 99%
“…An early report on CproCT claimed calcium-lowering and antiresorptive skeletal actions synergistic with CT (15). Other investigators and subsequently even the original reporting group found no CT-like actions for C-proCT (17,18).Recently, a 7-kDa 57-residue amino-terminal proCT cleavage peptide, N-proCT, was identified in rat and human C cells (19,20). Like C-proCT, N-proCT is secreted in equimolar amounts with CT (19).…”
mentioning
confidence: 99%
“…Although IAPPl_37 was identified as the major constituent of amyloid in the extracted samples of pancreatic tissue [1], the presence of pro-IAPP (or other fragments of pro-IAPP) in amyloid could not be excluded. Incomplete processing of procalcitonin at both the C-and N-terminals has been implicated in the amyloidosis associated with medullary carcinomas of the thyroid [6,7].…”
Section: Resultsmentioning
confidence: 99%